Access to hypertension care and services in primary health-care settings in Vietnam: a systematic narrative review of existing literature. Issue 1 (1st January 2019) - Meiqari, Lana; Nguyen, Thi-Phuong-Lan; Essink, Dirk; Zweekhorst, Marjolein; Wright, Pamela; Scheele, Fedde
ABSTRACT: Background : Health care in Vietnam is challenged by a high burden of hypertension (HTN). Since 2000, several interventions were implemented to manage HTN; it is not clear what is the status of patient access to HTN care. Objective : This article aims to perform a systematic narrative review of the available evidence on access to HTN care and services in primary health-care settings in Vietnam. Methods : Search engines were used to identify relevant records of scientific and grey literature. Data from selected articles were analysed using standardised spreadsheets and MaxQDA and following a framework synthesis methodology. Results : There has been increasing interest in research and policy concerning the burden of HTN in Vietnam, covering many aspects of access to treatment at the primary health-care level. Vietnam's National HTN Programme is managed as a vertical programme and its services integrated into the network of primary health-care facilities across the public sector in selected provinces. The Programme financed population-wide screening campaigns for the early detection of HTN among people above 40 years of age. There was no information on the acceptability of HTN health services, especially regarding the interaction between patients and health professionals. In general, articles reported good availability of medication, but problems in accessing them included: fragmentation and lack of consistency in prescribing medication between different levels and short timespans for dispensing medication at primary health-care facilities. There was limited information related to the cost and economic impact of HTN treatment. Treatment adherence among hypertensive patients based on four studies did not exceed 70%. Conclusions : Although the Vietnamese health-care system has taken steps to accommodate some of the needs of HTN patients, it is crucial to scale-up interventions that allow for regular, systematic, and integrated care, especially at the lowest levels of care.